I wish we could grab your image and touch you: A Sensory Approach to Laure Prouvost’s Work (AN-ICON. Studies in Environmental Images [ISSN 2785-7433], 2023)
This contribution investigates the notion of immersiveness in Laure Prouvost’s production, critically questioning the relationship between the environments designed by the French artist and the short film projected in them. More specifically, an attempt will be made to demonstrate how the activation of a sense of immersion depends on the fact that Prouvost’s hypermedia installations act as both environments (ambiente) and settings (ambientazione). This study demonstrates how the immersive condition that the artist’s film performance activates, while undoubtedly relating to the environmental context in which they appear, springs from a spectrum of strategies that Prouvost’s moving images orchestrate. These include the layered and plastic quality of the moving image; the relationships between word and image within intermediary storytelling; the montage as a critical tool; and, more precisely, bodies that are not necessarily human as the locus of sensitive knowledge. A theoretical framework that intersects the notion of the “system aesthetic,” Hugo Munsterberg’s prodromal psychological theory and multiple forms of haptic vision-resonance will define the guidelines of the argumentation, in parallel with tracing an inseparable art-historical genealogy to comprehend Laure Prouvost’s research.
Keywords: Laure Prouvost; Immersion; New media; Haptic perception; Film studies